The Effect Of Leverage, Company Size, Company Risk On Tax Avoidance In 2020-2022: Case Study of a Manufacturing Company in the Raw Materials Sector - Sari, Pascalia Indah Permata; Ramli, Abdul Haeba (Institut Bisnis dan Informatika Kesatuan, 2023)
The aim of this research is to see the effect of leverage, company size and company risk on tax avoidance. In this research, 18 companies were selected using purposive sampling criteria with a total of 54 objects studied in manufacturing companies in the raw materials sector during the period 2020 to 2022. The data used is secondary data in the form of financial reports obtained from the website www.idx.co .id was measured using the SPSS27 research tool with multiple linear regression analysis. The results of this research show that the variables leverage, company size and company risk have a positive and significant effect on tax avoidance. The R Square value is 44.8% of the variables leverage, company size and company risk, while the remaining 55.2% is influenced by variables outside this research. This research can provide insights and considerations for companies, it is recommended that they be careful in making decisions regarding increasing debt. This is because high debt can create risks that can result in companies facing potential bankruptcy and tax avoidance practices. Keywords : Leverage, Company Size, Company Risk and Tax Avoidance